Analisis Framing Nilai Anti Korupsi dalam Film Jimpitan - Nafi Ma'la, Ahmad Azka; Asiyah, Siti (Mu'ashir: Jurnal Dakwah dan Komunikasi Islam, 2023)
The Jimpitan film is one of the films that won the ACFFest event organized by the Corruption Eradication Commission. The Jimpitan film contains a story that represents the value of anti-corruption through the story of a farmer's struggle to replace the people's jimpitan rice. The focus of this study is to find out how the framing of anti-corruption values in the Jimpitan film. The anti-corruption value indicators are taken from the Nine Anti-Corruption Values formulated by the Corruption Eradication Commission. This research is a qualitative type of library research with Framing Analysis theory from Zong dang Pan & Gerald M. Kosicki. The results of the study show that the Jimpitan film contains four anticorruption values, namely responsibility, simplicity, independence and courage. This value is conveyed by the author through character building, storytelling and describing the efforts made by Poniman in replacing jimpitan rice.